Impression management and self-presentation dissimulation in Portuguese chairman's statements - Oliveira, J.; Azevedo, G.; Borges, F. (Corporate Communications: An International Journal, 2016)
Drawn on social psychology theory of impression management, the present study tries to assess the way Portuguese managers build their narratives in Chairman’s Statement to manage stakeholders’ perceptions on corporate image, in a period of time of scarce resources. The paper’s theoretical framework draws on elements of social psychology theory of impression management developed by Leary and Kowalski (1990). Through the use of the two-component model of impression management (impression motivation and impression construction) the 45 Chairmen's Statements of Portuguese non-finance companies were content analysed to understand how managers build their voluntary communication strategies. Results indicate that organizational outcome does not influence the adoption of impression management strategies. But public visibility and consumer proximity are crucial factors in explaining them. Larger companies with high consumer proximity present themselves in a favourable way, but consistent with an overall reading of the annual report. These companies show a higher level of verbosity, consistent to the argument of retrospective rationality. The present study goes beyond Merkl-Davies et al. (2011) work and obtains insightful knowledge on the influence of goal-relevance of impression in three different perspectives: company’s public visibility, company’s dependency from debtholders, and consumer proximity. Moreover, the analysis uses a period of scarce resources and a European Latin country, with no tradition in publishing Chairmen's Statements, but that recently has changed its financial reporting practices from an institutional code-law logic to an institutional common-law logic. A research setting like this has not been studied hitherto.